2007
DOI: 10.3327/jnst.44.958
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Treatment Based on Ultra-fine-group Spectrum Calculation in the AEGIS Code

Abstract: The resonance calculation method using the ultra-fine-group spectrum calculations in the AEGIS code is explained in detail. By a simple benchmark problem, it is verified that the effect of anisotropic scattering on effective cross-sections is not very large and the isotropic scattering source approximation is adequate in practical resonance calculations in LWRs. Furthermore, some efficient numerical algorithms in the ultra-fine-group calculations to reduce the computation time without large degeneration of acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…A resulting spectrum is used as a weighting function for condensation to the target group structure. However, this approximation-free method is not practical at all, and thus many approximated ways have been proposed [10,11,[46][47][48], to which the EDC method belongs. Instead of solving the slowing down problem in an explicit heterogeneous lattice geometry using the DFEM-SN solver, the heterogeneous lattice geometry is decoupled to multiple 1D pin-cell problems that preserve the Dancoff factor calculated in the reference geometry using the DFEM-SN solver.…”
Section: Equivalent Dancoff Factor Cell (Edc) Methodsmentioning
confidence: 99%
“…A resulting spectrum is used as a weighting function for condensation to the target group structure. However, this approximation-free method is not practical at all, and thus many approximated ways have been proposed [10,11,[46][47][48], to which the EDC method belongs. Instead of solving the slowing down problem in an explicit heterogeneous lattice geometry using the DFEM-SN solver, the heterogeneous lattice geometry is decoupled to multiple 1D pin-cell problems that preserve the Dancoff factor calculated in the reference geometry using the DFEM-SN solver.…”
Section: Equivalent Dancoff Factor Cell (Edc) Methodsmentioning
confidence: 99%
“…From the reproducibility of the SPH method, reaction rates at the mth burnup step obtained by the SPH method become equivalent to those obtained with a fine condition. Therefore, Equation (9), which describes the equivalence of reaction rates, is satisfied,…”
Section: Discretization Errors In the Sph Methodsmentioning
confidence: 99%
“…In this paper, a calculation scheme using the SPH method is considered as the first step of this study. The SPH method is a kind of equivalence methods, by which a reference result can be reproduced with a coarse calculation condition, and is used to improve calculation efficiency in the previous studies [8][9][10]. Although the SPH method is originally a technique for reducing spatial homogenization errors, the SPH method can be used also for reducing discretization errors due to coarse ray tracing condition as described above.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a coarse-energy group calculation does not reproduce neutron multiplication factor of a reference fine-energy group calculation even if fine-group neutron flux obtained from the reference calculation is used as a weight function in cross section group collapsing (Sugimura and Yamamoto, 2007).…”
Section: Corrections For Current-weighted Total Cross Sectionmentioning
confidence: 99%